Redesign of Facilities Layout Using Computerized Relationship Planning (CORELAP) and Computerized Relative Allocation of Facilities Techniques (CRAFT) Methods - Yuninda Wulan Sari; Chauliah Fatma Putri; Andy Hardianto (Widyagama University of Malang, 2023)
The Barokah Jaya Snack Industry is an MSME engaged in the manufacture of jipang rice and popcorn. Based on the results of direct observation, it is known that the main problem is operator complaints in picking up raw materials that are often used too far away and the placement is not close together so that the distance becomes long. This research looks for alternative solutions to problems in the scope of production in the Barokah Jaya Snack Industry, by making redesign proposals using the CORELAP (Computerized Relationship Layout Planning) and CRAFT (Computerized Relative Allocation of Facilities Technique) methods. The total displacement moment in the design using the CORELAP method is 1,978.75 meters/month, and in the design using the CRAFT method is 1,755.8 meters/month. The Material Handling Cost (OMH) for the design using the CORELAP method is Rp. 811,288/month and the design using the CRAFT method is Rp. 719,892/month. The layout resulting from the CORELAP method provides a material flow efficiency of 45.88% against the initial layout and the layout resulting from the CRAFT method provides a material flow efficiency of 51.98%. The selected layout recommendation has a total material displacement moment that is smaller than the initial layout and the smallest among the other alternative layouts. The selected layout is the layout designed using the CRAFT method, which is 1,755.8 meters/month increasing the efficiency of material flow by 51.98% and saving material transfer costs of Rp. 778,146/month.